Analisis Peran Keluarga dalam Pembentukan Perkembangan Emosional Anak Usia Dini : Peran Komunikasi Keluarga dalam Membentuk Stabilitas Emosi Anak - Rofiqotuz zahro; Ma'mun Hanif (Jurnal Inovasi Pendidikan dan Ilmu Sosial, 2025)
This study aims to analyze the role of the family in shaping the emotional development of early childhood, with a focus on parent-child interactions, parenting patterns, and emotional conditions within the family. A qualitative approach with a case study design was chosen to deeply understand the family dynamics that influence children's emotional development. A total of ten pairs of parents with children aged 3-5 years were selected using purposive sampling techniques. Data collection was carried out through in-depth interviews, observations, and the use of a Likert scale to measure parents' views on their role in supporting children's emotional development. The results showed that parental emotional support is very important in helping children manage their emotions. As many as 70% of respondents said that the emotional support they provide has a positive impact on children's ability to manage emotions. In addition, democratic parenting patterns that provide space for children to express their feelings also contribute significantly to children's emotional development, with 60% of respondents using this parenting pattern. Stable and positive family emotional conditions have been shown to be another important factor, where families with a supportive emotional atmosphere can help children manage stress and negative emotions better. This study confirms that the role of the family is very central in shaping the ability of early childhood to manage their emotions, with loving interactions, responsive parenting patterns, and a stable emotional atmosphere as the main factors.